PERAN PERPUSTAKAAN TERHADAP PELAKSANAAN PROGRAM PEMBELAJARAN DI SDIT SALSABILA 2 KLASEMAN YOGYAKARTA - Alifia Intan Sekar Sari; Ihda A’yunil Khotimah (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
Libraries have an important role in the field of education, for research purposes, preservation of information resources and recreation areas. Libraries also have a role in increasing the intelligence and empowerment of the nation, as a human person who always wants to advance and the development of institutions that are increasingly experiencing intense competition. This study seeks to see the role of the library in improving the quality of elementary schools at SDIT Salsabila 2 Klaseman, both with regard to student achievement and the progress of the institution. The type of research used is descriptive qualitative, data collection is done by looking directly at the object of research (direct observation) interviews and documentation. The results of this study indicate that libraries have an important role in improving the quality of elementary schools such as the development of library facilities; there is a special room, a growing collection of books, modern service systems, air-conditioned room facilities, computers and LCD projectors are available and also supports children's achievements in winning several championships including in the PAI quiz competition and the MIPA Olympiad